The Students’ Perceptions on English Teachers’ Teaching Style and How It Affects on Learning Motivation - Putri Nida Dewi, Ni Komang; Sulistia Dewi, Ni Luh Putu Eka; Suprianti, G.A.P. Suprianti (Universitas Pendidikan Ganesha, 2020)
This study used students’ perception to know their perception on the English teachers’ teaching style and how their perceptions affect their learning motivation in English. This study used survey method with questionnaire as the instrument that distributed to 342 students. The data was verified using interview method. The results were the students had good enough perceptions on the English teachers’ teaching style. Moreover, this result showed the students interested to learn English when the English teachers call the students by their nickname, use vocabulary that students easy to understand, give clear explanation and mastering the material, give clear instruction, demonstrate how to pronounce words, give a task to the students, ask the students to find out learning resource independently, explain material not only speech, ask the students to do discussion. Through this study, perhaps, the stakeholder makes policies to give a room such as workshops for the English teachers to know this case and encourage them in such a way, and then the English teachers can do the teaching style that makes the students interested in learning English to increase the students learning motivation.